2010
DOI: 10.1016/j.ijgo.2009.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of stage IA1 squamous cell carcinoma of the cervix with positive resection margins after conization

Abstract: Objective: To evaluate the efficacy of cold knife conization with electrocauterization and the feasibility of conservative management in patients with stage IA1 carcinoma of the cervix according to margin status after conization. Methods: Medical and histopathological records of 108 patients with stage IA1 cervical carcinoma were reviewed retrospectively. Patients underwent cold knife conization with electrocauterization or conization followed by hysterectomy. Disease recurrence was defined as a histologic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Persistent or recurrent cervical disease may occur in women with negative margins or those involved by SIL, and both groups remain at risk for persistent or recurrent SIL [98]. Women with involved margins are at increased risk for both the presence of multifocal invasive squamous carcinoma and persistent SIL [96,137,[139][140][141][142][143]. Clinical follow-up or immediate reexcision may be chosen in the management of women with SIL at the surgical margins.…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…Persistent or recurrent cervical disease may occur in women with negative margins or those involved by SIL, and both groups remain at risk for persistent or recurrent SIL [98]. Women with involved margins are at increased risk for both the presence of multifocal invasive squamous carcinoma and persistent SIL [96,137,[139][140][141][142][143]. Clinical follow-up or immediate reexcision may be chosen in the management of women with SIL at the surgical margins.…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…These studies defined residual disease as more than CIN II. Furthermore, residual disease in hysterectomy specimens was not found for women who had negative resection margins and was instead found only in those who had positive resection margins …”
Section: Discussionmentioning
confidence: 96%
“…The low risk of residual tumor has been observed in previous studies, particularly for stage IA1 squamous cell carcinomas with negative margins following conization . Previous investigators have found that the incidence of residual disease is significantly lower in patients with negative margins than in those with positive margins . Some reported that the risk of residual disease was 11.1% (3/27) for patients treated with a hysterectomy following conization in line with patients' wishes, with negative margins for cervical intraepithelial neoplasia (CIN) and no LVSI .…”
Section: Discussionmentioning
confidence: 99%
“…13 Patients who had CKC have better quality of life and sex than patients who had hysterectomy and RTas treatment of microinvasive cervical SCC. 14 It has been reported that important prognostic factors with early-stage cervical SCC are tumor volume, LVSI, and PLND. Most patients with clinical stage IA1 have small tumor, negative PLND, and negative LVSI.…”
Section: Discussionmentioning
confidence: 99%
“…As long as it fulfilled the requirements of fertility sparing, CKC could be the preferred surgery under close follow-up, and hysterectomy and PLND may not be required. 14,16 The National Comprehensive Cancer Network (NCCN) clinical practice guidelines on earlystage cervical SCC treatment recommendations were as following: the patients without lymph node invasion who have fertility requirements or were not suitable for hysterectomy should undergo fertility-sparing surgery (including CKC); and patients who have no fertility requirements could undergo hysterectomy. 17 We found that some young and nulliparous patients who had stage IA1 microinvasive cervical SCC with clear resection margins after CKC considered CKC operation as the final therapy.…”
Section: Discussionmentioning
confidence: 99%